Negotiating liminal identities in Mohja Kahf's The Girl in the Tangerine Scarf - Alkarawi, Susan Taha; Bahar, Ida Baizura (Australian International Academic Centre, 2013)
This paper challenges the thought that the term ‘Muslim woman’ connotes submissive or backward and is in need of rescue by the West through a literary analysis of the work by Mohja Kahf (b.1967), a leading contemporary Arab-American Muslim woman writer. In her novel, The Girl in the Tangerine Scarf (2006), Kahf focuses on the oppressive and discriminatory practices Muslim women encounter when wearing the hijab or veil where the main character and narrator experiences a type of identity split, or fragmentation, when assimilating into mainstream American culture. As a tool for analysis, the notion of liminality by Victor Turner (1920-1983), a British cultural anthropologist, is used to analyze the narrator’s choice of being ‘betwixt and between’ the state of things, or being ‘neither here nor there’. The resolution of social and personal conflicts portrayed is mapped to the stages of liminality.